The Students’ Obstacles in Speaking for Professional Context during Online Learning - Fauzul Etfita; Siti Hamidah; Berlian Agung Anugrah; Lusi Septari; Maya Dwi Sukma Fatania; Arimuliani Ahmad (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The teaching and learning process, particularly in Universities, was conducted face-to-face but has transitioned to fully online learning back in COVID-19 pandemic. Lecturers and students were forced to engage in online learning and teaching activities, which has a significant impact on the student's learning experience. This study is aimed to investigate students' difficulties in speaking for professional context class during the COVID-19 situation. The quantitative method was used and an online questionnaire was distributed to 30 students in the third-semester English Language Education of a private university in Riau. The findings revealed a number of issues that students encountered while taking the class. The first is the usage of YouTube videos as a source of educational materials. Next, the students have difficulty elaborating on the lecturer's material during online classes. After that, the issue concerns the student procedures when working on projects or assignments assigned by the lecturer. The fourth is overcoming students' access limitations to ZOOM Meetings. The last is the lack of learning equipment and student support services while participating in online learning.